Utilization of a fattigation platform gelatin-oleic acid sodium salt conjugate as a novel solubilizing adjuvant for poorly water-soluble drugs via self-assembly and nanonization - Kim, Dayoung; Park, Chulhun; Meghani, Nileshkumar M.; Tran, Thao T.D.; Tran, Phuong H.L.; Park, Jun Bom; Lee, Beom Jin (International Journal of Pharmaceutics, 2020)
Solubilizing adjuvants are commonly used to dissolve insoluble drugs by simply adding in a formulation. In this study, gelatin and oleic acid sodium salt (OAS), a generally recognized as safe-listed material were chosen and conjugated to develop a natural solubilizing adjuvant using the fattigation platform technology to enhance solubility and dissolution rate of poorly water-soluble drugs according to self-assembly and nanonization principle when simply mixed with poorly water-soluble drugs. We synthesized the gelatin and OAS conjugates (GOC) at three different ratios (1:1, 1:3, 1:5; GOC 1, GOC 2, and GOC 3, respectively) via the 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide/N-hydroxysuccinimide reaction using a spray dryer. This amphiphilic micronized GOC was self-assembled into nanoparticles. The synthesis of new amphiphilic conjugates was identified through Fourier transform-infrared (FT-IR) spectroscopy. The powder properties of the GOCs, such as angle of repose, bulk density, and tapped density were varied with the oleic acid bonding ratio. Then, GOCs were utilized to investigate the enhanced solubility and release rate of various poorly water-soluble drugs such as cilostazol (CSZ), coenzyme Q10, ticagrelor, telmisartan, aprepitant and itraconazole as model drugs. Based on the solubility studies by concentration and type of GOCs, 3% GOC 2 was selected. When this GOC was mixed with these model drugs by the physical mixing, wetting and hot melting methoods, the solubility was highly enhanced compared to the pure control drug, ranging from 20 to 150,000 times. In case of CSZ, all formulations were significantly improved release rate compared to the of CSZ alone and the reference tablet, cilostan® (Korea United Pharm) in simulated intestinal fluid containing 0.2% sodium lauryl sulfate. Differential scanning calorimetry and powder X-ray diffraction were conducted to confirm the crystal polymorphic structure of CSZ, and as a result they changed to diminutive peak intensity compared to CSZ alone. Field-emission scanning electron microscopy indicated that GOC was round with a reduced size of about 100 nm. The reduction of drug particles via nanonization and self-assembly of amphiphilic GOC in an aqueous media could be a key factor to improve poor water solubility by providing a favorable dispersion of drug molecules in an amphiphilic network.
Keywords: Adjuvants, Pharmaceutic; Aprepitant; Cilostazol; Drug Liberation; Gelatin; Intestinal Secretions; Itraconazole; Nanoparticles; Oleic Acid; Solubility; Telmisartan; Ticagrelor; Water; Fattigation platform; Gelatin-oleic acid conjugate (GOC); Initial solubility; Nanonization; Poorly water-soluble drugs; Self-assembly; Solubilizing adjuvant